2018
DOI: 10.1007/s00299-018-2303-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomic responses to gibberellic acid and 6-benzylaminopurine in Cunila menthoides Benth. (Lamiaceae): a contribution to understand the metabolic pathways

Abstract: Gibberellic acid elicited synthesis of many phenols from different classes and enhanced production of sesquiterpenoids, polyterpenoids, steroids and monoterpenoids compared to control and 6-benzylaminopurine. Little is known about the effects of 6-benzylaminopurine (BA) and gibberellic acid (GA3) on the synthesis of secondary metabolites in species of Lamiaceae. In this study, for the first time, the profile of secondary metabolites in plantlets of Cunila menthoides was characterized, using UPLC-ESI-Qq-oaTOF-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The precursor of salvinorins is geranylgeranyl diphosphate (GGPP), the biosynthesis of which occurs via the 2-C-methyl-erythritol 4-phosphate (MEP) pathway 46 , 47 . 6-benzyloaminopurine reduce the amount of compounds witch are biosynthesized on the MEP pathway 48 , similar as in our case. The other studies indicate the influence of NAA on the MEP pathway 49 , 50 .…”
Section: Discussionsupporting
confidence: 86%
“…The precursor of salvinorins is geranylgeranyl diphosphate (GGPP), the biosynthesis of which occurs via the 2-C-methyl-erythritol 4-phosphate (MEP) pathway 46 , 47 . 6-benzyloaminopurine reduce the amount of compounds witch are biosynthesized on the MEP pathway 48 , similar as in our case. The other studies indicate the influence of NAA on the MEP pathway 49 , 50 .…”
Section: Discussionsupporting
confidence: 86%
“…showed that the antioxidant activity of this constituent in sunflower oil was less active compared with caffeic acid. As for the plumerubroside, it was isolated from a water‐soluble extract of the stem bark of Plumeria rubra and also has been found in plantlets of Cunila menthoides and wheat ears at the flowering stage 81‐83 . Therishitin, a phytoalexin associated with plant defense, has been described in different Helianthus species as an antimicrobial compound 84 …”
Section: Discussionmentioning
confidence: 99%
“…As for the plumerubroside, it was isolated from a water-soluble extract of the stem bark of Plumeria rubra and also has been found in plantlets of Cunila menthoides and wheat ears at the flowering stage. [81][82][83] Therishitin, a phytoalexin associated with plant defense, has been described in different Helianthus species as an antimicrobial compound. 84 Adeleke and Babalola 74 and Guo et al 3 have reported phenolic compounds with distinct biological activities in sunflower seed and by-products.…”
Section: Untargeted Metabolomic Analysis and Phytochemical Profile Of...mentioning
confidence: 99%